2001
DOI: 10.1159/000056146
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Silymarin MZ-80 on Hepatic Oxidative Stress in Rats with Biliary Obstruction

Abstract: This study was designed to evaluate the effects of three pharmaceutical forms of silymarin (silymarin MZ-80, silybinin-β-cyclodextrin, and silybinin) on the liver oxidative status in vitro and after oral administration to rats with extrahepatic biliary obstruction (EBO) and sham-operated animals. We evaluated thiobarbituric acid-reactive substances (TBARS), glutathione (GSH + GSSG) and their related enzyme activities (GSH peroxidase, GSSG reductase and GSH transferase). All three compounds inhibited the in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 31 publications
1
10
1
Order By: Relevance
“…The elevation in the status of vitamin E during SIL treatment indicated the antioxidant and free radical scavenging potential of SIL. The protective effects of SIL observed in this study are in accordance with the investigations of Gonzalez-Correa et al (2002), who observed the antioxidant effect of SIL against oxidative stress in rat brain. Further, Zielinska-Przyjemska and Wiktorowicz (2006) have also shown that silydianin, an important and major constituent of SIL, possesses excellent in vitro free radical scavenging activity.…”
Section: Discussionsupporting
confidence: 92%
“…The elevation in the status of vitamin E during SIL treatment indicated the antioxidant and free radical scavenging potential of SIL. The protective effects of SIL observed in this study are in accordance with the investigations of Gonzalez-Correa et al (2002), who observed the antioxidant effect of SIL against oxidative stress in rat brain. Further, Zielinska-Przyjemska and Wiktorowicz (2006) have also shown that silydianin, an important and major constituent of SIL, possesses excellent in vitro free radical scavenging activity.…”
Section: Discussionsupporting
confidence: 92%
“…Genes related to antioxidation and liver functions were identified based on KEGG pathway database. 7 Previous reports indicated that silymarin exhibits antioxidant activity partly through restoration of intracellular glutathione levels and activation of antioxidation-related enzymes involved in druginduced and carcinogen-induced hepatotoxicity (20,29,30). Indeed, the intracellular glutathione levels of hepatocytes were significantly increased after silymarin treatment (Fig.…”
Section: Cancer Researchmentioning
confidence: 91%
“…Similarly, the bile salts (BSs) retained in cholestatic disorders due to the secretory failure are though to produce in part damaging effects by inducing oxidative stress [27,28], and SIL may counteract these harmful effects. This has been recently corroborated in experimental bileduct ligation, where SIL improves the antioxidant status of obstructed livers and prevents lipid peroxidation [29,30]. Oxidative stress is a major feature of alcoholic and non-alcoholic liver steatosis, and a key determinant of their progression to cirrhosis.…”
mentioning
confidence: 78%